Toward 2D grating coupler enabled O-band coherent links based on SiGe photonic electronic technology. (24th February 2023) - Zimmermann, Lars; Seiler, Pascal M.; Mai, Christian; Georgieva, Galina
Abstract: Coherent techniques for short reach intra-datacenter optical interconnects are currently intensely discussed. This article reports progress on previous work that analyzed the benefits of switching from C- to O-band optics with regard to digital signal processing. Here we study the feasibility of adapting a coherent approach to an established datacenter interconnect technology (PSM4). This PSM4-like implementation brings about the benefit of much improved resilience to laser drift, thus reducing or eliminating the need for a temperature stabilized laser, which is typically assumed a requirement for coherent transceivers. The analysis rests on simulation parameters derived in part from previous experimental realizations of coherent receivers in SiGe photonic BiCMOS technology. In addition, we make use of recent results regarding the optimization of O-band 2D grating couplers with respect to efficiency and low polarization dependence over a 20 nm wavelength window. We identify such couplers as enabling building blocks for coherent PSM4-like implementations.